Buckling Analysis of FG Porous Truncated Conical Shells Resting on Elastic Foundations in the Framework of the Shear Deformation Theory (Advances in Applied Mathematics and Mechanics, 2021)
In this article, an analytical method is proposed to analyze of the linear buckling behavior of the FG porous truncated conical shells subjected to a uniform axial compressive load and resting on the Pasternak elastic foundation. The material properties including Young's modulus, shear modulus and density are assumed to vary in the thickness direction. Three types of FG porous distributions including symmetric porosity distribution, non-symmetric porosity and uniform porosity distribution are considered. The governing equations of the FG porous truncated conical shells are obtained by using the first-order shear deformation theory (FSDT). With the help of the Galerkin method, the expressions for critical buckling loads are obtained in closed forms. The reliability of the obtained results is verified by comparing the present solutions with the published solutions. Finally, the numerical results show the effects of shell characteristics, porosity distribution, porosity coefficient, and elastic foundation on the critical buckling load.